In-virtro test of a stentless pericondial attached commissures (SPAC) valve - Ko, Zi Kai. (2010)
Occurrences of aortic valve disease is increasing worldwide, concomitant with the ageing of the general population and the habitual consumption of diets high in calories and cholesterol. Aortic valve replacement surgery is the most efficient solution to aortic valve diseases. The clinical results show that stentless biological prostheses provide a better haemodynamic performance and fewer complications compared with their mechanical counterparts. Advancements in aortic valve replacements saw the materialization of the truly-stentless aortic bioprosthetic valves with full pericardial constructs and the Single Point Attached Commissure implantation (SPAC) technique. The SPAC technique involves suturing the base of the valve to the aortic annulus in a circular line and the commissures attached to the aortic wall at the level of sinotubular junction at three single points, which greatly simplifies the implantation procedure.